Estimates of Arab world research productivity associated with desalination: a bibliometric analysis. Issue 1 (December 2015) - Zyoud, S. H.; Fuchs-Hanusch, D.
Abstract : Arab world is facing severe water scarcity. This hot issue is the driving force behind investing heavily in desalination, the backbone of the water sector. A bibliometric analysis based on databases from Scopus has been conducted to track research activities in this field. This study aimed to dissect research productivity, collaboration, citations and fields of interests. A total of 1075 documents about 'desalination' were published from Arab world, which represents 16·0% of the global research. The highest number of articles was from Saudi Arabia (28·1%), followed by Egypt (15·6%). The total number of citations was 9922. The average was 9·23 citations/document. h -index was 42, and the highest one was 24 for Saudi Arabia. The most productive journal was Desalination. The study identified 270 (25·1%) documents with 31 countries in Arab–foreign country collaborations. The most productive institution was King Saud University, Saudi Arabia. The present data reveal a promising rise and renaissance in desalination research.